2023
DOI: 10.1097/gh9.0000000000000104
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of neuroinfectious diseases and outcomes in Africa

Abstract: Neuroinfectious diseases are infections affecting the central and peripheral nervous system, possibly due to bacterial, viral, fungal, or parasitic infections [1] . The route of infection to the nervous system could be through direct inoculation, blood circulation, retrograde spread, or others [2] . Central nervous system infections are often challenging to diagnose, and the burden of undiagnosed nervous system infections is currently underreported; despite the recent advances in investigative technology, abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…One or two of these features indicate a precursor state, three or more of these features indicate frailty, and none indicate no frailty [7]. Frailty is a concept that has been used to determine surgical outcomes in older patients; therefore, it becomes a crucial factor in Africa's practice of neurological surgery, as a result of increased life expectancy in the continent and increase usage of neurosurgical services [8][9][10][11] With expanding population of elderly people in the world and Africa, improving neurosurgical care to this age group becomes paramount, and frailty studies are important tools in ensuring improved neurosurgical service delivery to elderly people in Africa. Wojda et al reported an increase in the population of elderly patient that are presenting in the accident and emergencies in sub-Saharan Africa over the period of 1989-2014, as seen in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…One or two of these features indicate a precursor state, three or more of these features indicate frailty, and none indicate no frailty [7]. Frailty is a concept that has been used to determine surgical outcomes in older patients; therefore, it becomes a crucial factor in Africa's practice of neurological surgery, as a result of increased life expectancy in the continent and increase usage of neurosurgical services [8][9][10][11] With expanding population of elderly people in the world and Africa, improving neurosurgical care to this age group becomes paramount, and frailty studies are important tools in ensuring improved neurosurgical service delivery to elderly people in Africa. Wojda et al reported an increase in the population of elderly patient that are presenting in the accident and emergencies in sub-Saharan Africa over the period of 1989-2014, as seen in Fig.…”
Section: Introductionmentioning
confidence: 99%